2005
DOI: 10.1074/jbc.m504137200
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Synaptic Vesicle Pools in Mature Central Nerve Terminals

Abstract: Readily releasable and reserve pools of synaptic vesicles play different roles in neurotransmission, and it is important to understand their recycling and interchange in mature central synapses. Using adult rat cerebrocortical synaptosomes, we have shown that 100 mosM hypertonic sucrose caused complete exocytosis of only the readily releasable pool (RRP) of synaptic vesicles containing glutamate or ␥-aminobutyric acid. Repetitive hypertonic stimulations revealed that this pool recycled (and reloaded the neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 57 publications
5
25
0
Order By: Relevance
“…AP-3B is also required to generate synaptic vesicles in presynaptic endosomes (22). PI4K2␣ is the only PI4K isozyme found in synaptic vesicles, which also contain PtdIns (17,24,25), and both PI4K2␣ and AP-3 have been implicated in formation of the reserve pool (26,27). However, studies based on inhibition of synaptosome function have produced conflicting results concerning a role for PI4K2␣ in neurotransmitter release (24,26,28).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…AP-3B is also required to generate synaptic vesicles in presynaptic endosomes (22). PI4K2␣ is the only PI4K isozyme found in synaptic vesicles, which also contain PtdIns (17,24,25), and both PI4K2␣ and AP-3 have been implicated in formation of the reserve pool (26,27). However, studies based on inhibition of synaptosome function have produced conflicting results concerning a role for PI4K2␣ in neurotransmitter release (24,26,28).…”
Section: Discussionmentioning
confidence: 98%
“…PI4K2␣ is the only PI4K isozyme found in synaptic vesicles, which also contain PtdIns (17,24,25), and both PI4K2␣ and AP-3 have been implicated in formation of the reserve pool (26,27). However, studies based on inhibition of synaptosome function have produced conflicting results concerning a role for PI4K2␣ in neurotransmitter release (24,26,28). Although detailed studies are needed to comprehensively assess synaptic vesicle function, our preliminary studies on synaptosomes from age-matched Pi4k2a GT/GT and WT mice revealed attenuated glutamate uptake but no difference in glutamate release.…”
Section: Discussionmentioning
confidence: 99%
“…This previous finding is in line with our observation that reserve pool vesicles do not significantly contribute to neurotransmission at high frequencies. Preferential recycling of RRP vesicles back to their pool of origin have been observed in dissociated hippocampal cultures (Pyle et al, 2000;Sara et al, 2002) as well as in cortical synaptosomes obtained from adult rats brains (Ashton and Ushkaryov, 2005). In addition, endocytosis gets accelerated with Ca 2ϩ influx in the calyx of Held terminal in the auditory brainstem as well as in dissociated hippocampal cultures (Sankaranarayanan and Ryan, 2001), presumably to support rapid reuse of at least some of the RRP vesicles (but see Li et al, 2005;Zenisek, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…3, A and D). This does not happen in response to sucrose, a nonphysiological hypertonic treatment known to produce repeatable NT release in a Ca 2ϩ -dependent manner (41). We found that sustained osmotic shock enhanced the respiration of d PC12 cells in a two-phase mode: the first, which is regulated by i Ca 2ϩ and can be inhibited by BAPTA-AM, and the second, which starts 10 min after sucrose application and can be abolished by chelation of i Ca 2ϩ or e Ca 2ϩ (Fig.…”
Section: Discussionmentioning
confidence: 99%